1996
DOI: 10.1021/jp960733z
|View full text |Cite
|
Sign up to set email alerts
|

Intrazeolite Photochemistry. 16. Fluorescence of Methylviologen Adsorbed within Medium- and Large-Pore Zeolites

Abstract: Methylviologen (MV 2+ ) incorporated within medium-and large-pore zeolites (NaZSM-5, Namordenite, NaY, and CsY) emits fluorescence at 330 and 420 nm; the latter is most prominent in zeolite NaY. The intensity ratio between these two bands depends on the structure of the zeolite. On the basis of molecular modeling and 13 C CP/MAS NMR using the dipolar dephasing technique, the first band has been ascribed to the emission of MV 2+ in a planar conformation. The unprecedented 420 nm band has been attributed to a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…[ 2 ] Along our exploratory studies on molecule-based multifunctional magnetic materials, [ 8 ] which date back to the pioneering work of Kahn and co-workers on oxamato-based heterobimetallic magnets, [ 9 ] we present herein the synthesis, crystal structure, thermal and sorption behavior, optical and magnetic properties of a new manganese(II)-copper(II) 2D MOF of formula MV[Mn 2 Cu 3 (mpba) 3 (H 2 O) 3 ] · 20H 2 O ( 1 ), where MV 2 + is the methylviologen dicationic dye [ 10 ] and mpba 4 − is the N,N′ -1,3-phenylenebis(oxamate) bridging ligand ( Scheme 1 ). Compound 1 exhibits highly selective gas sorption ability, luminescence capacity, and long-range magnetic ordering, constituting thus a unique example of luminescent porous magnet with potential applications in host-guest chemical sensing of small molecules.…”
Section: Doi: 101002/adma201201846mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 2 ] Along our exploratory studies on molecule-based multifunctional magnetic materials, [ 8 ] which date back to the pioneering work of Kahn and co-workers on oxamato-based heterobimetallic magnets, [ 9 ] we present herein the synthesis, crystal structure, thermal and sorption behavior, optical and magnetic properties of a new manganese(II)-copper(II) 2D MOF of formula MV[Mn 2 Cu 3 (mpba) 3 (H 2 O) 3 ] · 20H 2 O ( 1 ), where MV 2 + is the methylviologen dicationic dye [ 10 ] and mpba 4 − is the N,N′ -1,3-phenylenebis(oxamate) bridging ligand ( Scheme 1 ). Compound 1 exhibits highly selective gas sorption ability, luminescence capacity, and long-range magnetic ordering, constituting thus a unique example of luminescent porous magnet with potential applications in host-guest chemical sensing of small molecules.…”
Section: Doi: 101002/adma201201846mentioning
confidence: 99%
“…In fact, a fast radiationless deactivation pathway of the singlet excited state of the methylviologen cation and a subsequent non-emissive decay were earlier attributed to signifi cant rotation around the single bond connecting the two pyridinium rings. [ 10 ] The MV 2 + cations are quite isolated from each other [the shortest MV 2 + … MV 2 + distance is 7.768(11) Å for N(8)-N(8f)]. However, they establish weak intermolecular (van der Waals and/or electrostatic) interactions among their pyridinium-nitrogen and the carboxylate-oxygen atoms which are coordinated to the Cu II ions of the anionic network [N … O contacts in the range of 3.304(13)-3.368(10) Å] ( Figure S3).…”
Section: Doi: 101002/adma201201846mentioning
confidence: 99%
See 1 more Smart Citation
“…Among several different functional groups reported in the literature, there is considerable interest in the use of 4,4 0 -bipyridine derivatives to modify the surface of mesoporous silicas because of their interesting and well-known electron acceptor, charge transfer and fluorescence properties [24][25][26]. The quaternary salts of 4,4 0 -bipyridine, commonly known as viologen, are widely used as anion exchange groups in membranes [27], thermosensors [28], colorimetric sensors [29], for photocatalytic hydrogen evolution [30], for the design of optical materials [31] and for fluorescence probing [32].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that not only the electrochemical one-electron reduction potentials of these viologens were altered when compared to parent paraquat (1) but also the spectral characteristics (absorption maxima and molar extinction coefficients) of the formed radical cations. The situation becomes even more interesting when investigating the fluorescence of viologens (especially the ones of low molecular weight), a research topic which has been debated for a long time [1,[26][27][28]. The prevailing belief has been that viologens are non-fluorescent [1].…”
mentioning
confidence: 99%